2014
DOI: 10.1369/0022155414559590
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Development of the Mouse Thoracic Aorta Three-Dimensional Macromolecular Structure using Two-Photon Microscopy

Abstract: SummaryUsing the intrinsic optical properties of collagen and elastin, two-photon microscopy was applied to evaluate the threedimensional (3D) macromolecular structural development of the mouse thoracic aorta from birth to 60 days old. Baseline development was established in the Scavenger Receptor Class B Type I-Deficient, Hypomorphic Apolipoprotein ER61 (SR-BI KO/ApoeR61 h/h ) mouse in preparation for modeling atherosclerosis. Precise dissection enabled direct observation of the artery wall in situ. En-face, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To date, some laboratories have used this technique to image aortic samples in a conventional transverse perspective (XZ or YZ axes) 25 , 28 , as in standard histological preparations. A few other groups have applied multiphoton microscopy to image the tissue in an en-face view, and subsequently generated a three-dimensional rendering of it 29 , 30 . The en-face histological perspective consists of visualizing the surface of the vessel (XY axes) along the depth of its wall.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some laboratories have used this technique to image aortic samples in a conventional transverse perspective (XZ or YZ axes) 25 , 28 , as in standard histological preparations. A few other groups have applied multiphoton microscopy to image the tissue in an en-face view, and subsequently generated a three-dimensional rendering of it 29 , 30 . The en-face histological perspective consists of visualizing the surface of the vessel (XY axes) along the depth of its wall.…”
Section: Introductionmentioning
confidence: 99%
“…Early research by Roach and Burton suggested the contributions of compliant elastin fibers at lower levels of stress and stiff collagen fibers at higher levels of stress result in the nonlinear mechanics of the arterial wall [19]. Arterial structure-function has since been further explored from the macro-to nanoscale with the advancement of experimental approaches including mechanical characterization and optical imaging [20][21][22][23][24], and in computational modeling [25][26][27]. Alterations in structure and function to the arterial wall due to various pathological conditions are also being extensively studied, with the goal of early diagnosis, prevention, and the development of treatment options [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…CARS signal in context with the cellular structures of the biological sample (15,16). For the remainder of this study all CARS images were generated with fs pulses.…”
Section: Resultsmentioning
confidence: 99%